The Electronic Brain / How It Works - Cook Joseph J (G.P. Putnam'S Sons, 1969)
The Age of the Electronic Brain, The Beginning of Computers, The Arithmetic of Electronic Computers, Inside the Electronic Brain, National Defense and Space, Electronic Brains in Our Daily Lives, The Future, Glossary, Index.